2013
DOI: 10.1371/journal.pone.0053312
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of CD163 Expressing Phagocytic Chondrocytes in Joint Cartilage and Its Novel Scavenger Role in Cartilage Degradation

Abstract: BackgroundCartilage degradation is a typical characteristic of arthritis. This study examined whether there was a subset of phagocytic chondrocytes that expressed the specific macrophage marker, CD163, and investigated their role in cartilage degradation.MethodsCartilage from the knee and temporomandibular joints of Sprague-Dawley rats was harvested. Cartilage degradation was experimentally-induced in rat temporomandibular joints, using published biomechanical dental methods. The expression levels of CD163 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 30 publications
3
42
0
1
Order By: Relevance
“…It has been reported that although the soft diet plays a negative role in condyle development 5,9,10 , rabbits or rats that received TMJ discectomy had less degenerative cartilage changes 43,44 and higher condylar cartilage sulfate uptake 45 when fed with soft diet. Besides catabolic changes, the chondrocytes in mechanically induced degraded articular cartilage displayed the reparative capability, including the activities of phagocytizing dead cells 46 and proliferation 26,33,36,37 . Hence, there might be a stronger repair response in TMJ cartilage in the small-size diet than the large-size diet group while the mice received the same kind of abnormal prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that although the soft diet plays a negative role in condyle development 5,9,10 , rabbits or rats that received TMJ discectomy had less degenerative cartilage changes 43,44 and higher condylar cartilage sulfate uptake 45 when fed with soft diet. Besides catabolic changes, the chondrocytes in mechanically induced degraded articular cartilage displayed the reparative capability, including the activities of phagocytizing dead cells 46 and proliferation 26,33,36,37 . Hence, there might be a stronger repair response in TMJ cartilage in the small-size diet than the large-size diet group while the mice received the same kind of abnormal prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Primary rat chondrocytes were isolated as described previously [40]. In brief, chondrocytes were isolated from the condylar cartilage of 3-week-old female rat TMJs by digestion with 0.25% trypsin (Hyclone, Logan, UT, USA) for 20 min, followed by digestion with 0.2% type II collagenase (Invitrogen) for 2 h. Chondrocytes were resuspended in Dulbecco’s modified Eagle’s medium (DMEM, Hyclone) containing 10% fetal bovine serum (Hyclone) and then cultured in a fully humidified atmosphere with 5% CO 2 at 37°C for 3 days before use.…”
Section: Methodsmentioning
confidence: 99%
“…Some have proposed that, having isolated chondrocytes from degenerated rat cartilage, that phagocytosis could be handled by chondrocytes displaying a dedicated phenotype (i.e., type II collagen + /CD163 + ), in which phagocytic activity was measured, suggesting a role in the clearance of apoptotic and necrotic cells [103]. Hashimoto and coworkers demonstrated that apoptotic bodies derived from chondrocytes, treated with sodium nitroprusside (SNP) or anti-Fas, contained both nucleotide pyrophosphohydrolase (NTPPH) and alkaline phosphatase activities and could precipitate Ca ++ [104].…”
Section: Apoptosis In Chondrocytes and Osteoarthritis (Oa) Developmentioning
confidence: 99%